The effects of compound probiotics on production performance, rumen fermentation and microbiota of Hu sheep - Wang, Lijun; Lv, Zhanqi; Ning, Xiaodong; Yue, Zhiguang; Wang, Ping; Liu, Chaoqi; Jin, Sanjun; Li, Xinxin; Yin, Qingqiang; Zhu, Qun; Chang, Juan (Frontiers in Veterinary Science, 2024)
Fungal probiotics have the potential as feed additives, but less has been explored in ruminant feed up to date. This study aimed to determine the effect of compound probiotics (CPs) with Aspergillus oryzae 1, Aspergillus oryzae 2 and Candida utilis on Hu sheep’s growth performance, rumen fermentation and microbiota. A total of 120 male Hu sheep, aged 2 months and with the body weight of 16.95 ± 0.65 kg were divided into 4 groups. Each group consisted of 5 replicates, with 6 sheep per replicate. Group A was the control group fed with the basal diet. Group B, C and D was supplemented with the basal diet by adding 400, 800 and 1,200 grams per ton (g/t) CPs, respectively. The feeding trial lasted for 60 days after a 10-day adaptation period. The results showed that the average daily gain (ADG) of sheep in the CPs groups were significantly higher, the feed/gain were significantly lower than those in group A in the later stage and the overall period. The addition of CPs increased the economic benefit. The levels of CD4+ and the CD4+/CD8+ ratio in the CPs groups were higher than those in Group A. The levels of GSH, IgG, IL-2, IL-6, and IFN-γ in group C were significantly elevated compared with group A. Group B showed a significant increase in rumen NH3-N and cellulase activity. There was no difference in VFAs content between group A and group B, however, with the increasing addition of CPs, the butyric acid and isobutyric acid content tended to decrease. The rumen microbiota analysis indicated that the CPs addition increased the Firmicutes and Proteobacteria abundances, decreased the Bacteroidetes abundance. The correlation analysis showed that Prevotella was negatively correlated with ADG, and the addition of 400 CPs in group B reduced Prevotella’s relative abundance, indicating CPs increased sheep growth by decreasing Prevotella abundance. The CPs addition reduced caspase-3, NF-κB and TNF-α expression in liver, jejunum and rumen tissues. In conclusion, the addition of CPs increased the sheep production performance, reduced inflammation, improved rumen and intestinal health. Considering the above points and economic benefits, the optimal addition of CPs as an additive for Hu sheep is 800 g/t.